2008
DOI: 10.1080/00016340801976079
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes of women with pruritus, normal bile salts and liver enzymes: a case control study

Abstract: This study suggests that women who have transient pruritus with normal bile salts and liver biochemistry appear to have higher intrapartum and postpartum complications and require increased vigilance. In order to evaluate this finding, further prospective studies will be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…In the present study, maximum number of babies (92.9%) had Apgar score >7 at 5 minutes. This correlates well with the studies by Wai Yoong et al (2008), Apgar score >7 at 5 minutes was found in 99% of cases and the mean Apgar score at 5 minutes was 8.9. 24 Elisabeth Wikstrom et al (2010) reported that all babies in OC groups had Apgar score >9 at 5 minutes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, maximum number of babies (92.9%) had Apgar score >7 at 5 minutes. This correlates well with the studies by Wai Yoong et al (2008), Apgar score >7 at 5 minutes was found in 99% of cases and the mean Apgar score at 5 minutes was 8.9. 24 Elisabeth Wikstrom et al (2010) reported that all babies in OC groups had Apgar score >9 at 5 minutes.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of Low Birth Weight (LBW) babies was 8.5%. Similar results were found by the Wai Yoong et al (2008); 24 Sidhu et al 2008; 23 Dang Arbinder et al 2010; 21 i.e. 3.2 kg, 2.7 kg, 2.9 kg, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…A total of 13 studies [[13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25]] met the inclusion criteria Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Five case-control [13,14,18,19,25] and eight cohort studies [[15], [16], [17],[20], [21], [22], [23], [24]]. The included studies were published between 1994 to 2016 and originated from different parts of the world including; Australia, China, Finland, India, Mexico, Saudi Arabia, Sweden, Switzerland, United Kingdom and The United States of America.…”
Section: Resultsmentioning
confidence: 99%
“…Intrahepatic cholestasis of pregnancy (ICP) is a rare liver disorder which usually manifests in the third trimester. 1 2 3 4 5 ICP commonly presents with severe pruritus and elevated liver function tests. The pruritus may precede physical or laboratory abnormalities and is characterized by total body itching with predominance for the palms and soles of the feet.…”
mentioning
confidence: 99%